How culture shaped the human genome: bringing genetics and the human sciences together - Laland, Kevin N.; Odling-Smee, John; Myles, Sean (Nature reviews. Genetics, 2010)
Key Points A variety of researchers are converging on the view that human evolution has been shaped by gene–culture interactions. Theoretical biologists use models to demonstrate that cultural processes can affect human evolution, anthropologists are investigating cultural practices that modify current selection, and geneticists are uncovering alleles that have been subject to recent selection because of human activities. Theoretical population genetics models are used to explore how genes and culture interact over evolutionary time, including how and why culture can affect evolutionary rates. Niche-construction theory is a branch of evolutionary biology that emphasizes the capacity of organisms to modify natural selection and thereby act as co-directors of their own, and other species', evolution. Humans are the ultimate niche-constructing species. We specify how variation in buffering through cultural niche construction could explain geographical variation in human genes. A further source of evidence for gene–culture co-evolution comes from anthropological studies of contemporary human populations, which demonstrate gene–culture co-evolution in action. Examples include Kwa-speaking yam cultivators in West Africa whose agriculture favoured the haemoglobin S ( HbS ) 'sickle-cell' allele, and Polynesian voyages that led to positive selection for thrifty metabolism, leading to type 2 diabetes susceptibility. Geneticists have recently developed methods to identify alleles that have been favoured by recent selection, many of which seem to have been favoured because of cultural activities. Overrepresented categories of genes that have been subject to positive selection include those related to recent changes in human diet and human-induced disease. The well-researched example of co-evolution of dairy farming and the lactase gene shows the range of methods used to investigate gene–culture co-evolution. We end by asking how prevalent gene–culture co-evolution is, and how researchers can differentiate between a molecular signature of selection generated by gene–culture co-evolution and one generated from a non-cultural aspect of the environment. Theoretical, anthropological and genetic studies suggest that human evolution has been shaped by gene–culture interactions. This Review collates data from these diverse fields, and highlights the potential for cross-disciplinary exchange to provide novel insights into how culture has shaped the human genome. Researchers from diverse backgrounds are converging on the view that human evolution has been shaped by gene–culture interactions. Theoretical biologists have used population genetic models to demonstrate that cultural processes can have a profound effect on human evolution, and anthropologists are investigating cultural practices that modify current selection. These findings are supported by recent analyses of human genetic variation, which reveal that hundreds of genes have been subject to recent positive selection, often in response to human activities. Here, we collate these data, highlighting the considerable potential for cross-disciplinary exchange to provide novel insights into how culture has shaped the human genome.